FORMATIVE RESEARCH: PERCEPTIONS OF COMMUNICATION SCIENCE STUDENTS AT A PERUVIAN UNIVERSITY - Esquivel-Grados, José (2023)
Formative research generates different perceptions in undergraduate students, and in order to know more about them, 80 were surveyed, and 12 Communication Science students were interviewed at a national university in Lima (Peru). The results evidence that they conceive of it as: training to conduct scientific research, curricular or extracurricular activities as part of or for scientific research, preparation for conducting research work for graduation or obtaining a qualification, the development of competences for researching in the profession, an instructional strategy to develop research competences, and a strengthening of the research culture, among others. But beyond these varied concepts, the estimation of the majority emerges that formative research has been neglected by the university, thus becoming a challenge to optimize professional training, requiring qualified instructors with pertinent instructional methods, as well as an updated curriculum, which strengthens the research culture, responding to social demands and ensuring resources for the development of research competences.